2014
DOI: 10.1111/j.2047-2927.2014.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple proteins from ejaculated and epididymal porcine spermatozoa bind glycan motifs found in the oviduct

Abstract: SUMMARYPreviously, we demonstrated that porcine spermatozoa bind selectively to Lewis x (Le X ) and bi-antennary a2-6 sialylated N-acetyllactosamine (bi-SiaLN) glycan motifs found in the oviduct. Recognition of these motifs mediates sperm binding to oviduct epithelial cells to form a reservoir. Here, we characterize proteins that bind to Le X and bi-SiaLN in ejaculated and cauda epididymal spermato-) and bi-SiaLN were used to locate the binding proteins on spermatozoa. Binding to N-acetyllactosamine (LN), a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Data presented here support the hypothesis that multiple proteins coordinate binding to suLe X and potentially mediate sperm adhesion to the oviduct. This is in agreement with previous data from our group (Silva et al ., 2014) that has shown that multiple glycan-binding proteins recognize suLe X and bi-SiaLN motifs and some of these glycan-binding proteins are present before sperm contact with accessory gland fluids. While multiple proteins appear to bind suLe X , in the present work we have purified and identified ADAM5 and lactadherin as suLe X -binding proteins.…”
Section: Discussionsupporting
confidence: 94%
“…Data presented here support the hypothesis that multiple proteins coordinate binding to suLe X and potentially mediate sperm adhesion to the oviduct. This is in agreement with previous data from our group (Silva et al ., 2014) that has shown that multiple glycan-binding proteins recognize suLe X and bi-SiaLN motifs and some of these glycan-binding proteins are present before sperm contact with accessory gland fluids. While multiple proteins appear to bind suLe X , in the present work we have purified and identified ADAM5 and lactadherin as suLe X -binding proteins.…”
Section: Discussionsupporting
confidence: 94%
“…To characterize proteins on the plasma membrane of boar sperm that recognize Le X and bi-SiaLN motifs, sperm membrane proteins were separated by SDS-PAGE, transferred to nitrocellulose and incubated with biotinylated glycans, a 'glycan blot'. This analysis showed that sperm contained a very distinct group of proteins that recognized Le X migrating with molecular weights ranging between 12 and 250 kDa (Silva et al 2014). Binding of Le X was reduced when the Ca 2+ chelator EGTA was added, indicating that binding to at least some putative glycan receptors was Ca 2+dependent.…”
Section: Receptors On Sperm For Oviduct Glycansmentioning
confidence: 96%
“…The 12–15 kDa proteins were absent from this preparation, and four bands from 30 to 44 kDa and two bands at 37 and 44 kDa were present that bound Le X and bi‐SiaLN, respectively (Silva et al. ). Based on similar migration during SDS‐PAGE, it appears that some proteins may recognize both glycans.…”
Section: Function Of the Oviduct Epithelium In Sperm Binding And Storagementioning
confidence: 97%
See 1 more Smart Citation
“…3,4,1013 Glycoproteins expressing Le X have been identified as early mediators of the immune response against invading pathogens, 6,14,15 and are pivotal in immunomodulation, 6,1619 regulation of the growth and angiogenesis of tumor cells, 1,4 embryogenesis of the central nervous system 3,10,11 and promotion of the formation of a spermatozoa reservoir and subsequent release from the oviduct. 2022 DC-SIGN (dendritic cell specific ICAM grabbing non-integrin) is a counter-receptor to many Le X bearing glycoproteins, including CEACAM-1, Mac-1 and ICAM3, as well as unidentified Le X glycoproteins on invading pathogens and neutrophils. 2,7,9,2327 In turn, the interaction of dendritic cells and neutrophils enables antigen-presenting cells to stimulate T cells and modulate adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%